Pemanfaatan Tandan Kosong Kelapa Sawit (Tkks) Sebagai Arang Aktif Untuk Penjernihan Air di Desa Muara Sebapo Kecamatan Mestong Kabupaten Muaro Jambi - Muis, Lince; Anggraini, Febri Juita; Viareco, Hariestya; Wijaya, Dhian Eka (Fakultas Sains dan Teknologi, Universitas Jambi, 2023)
The need for clean water in Muara Sebapo Village remains a serious issue to this day. The water obtained by the community from dug wells or boreholes often appears yellow and has an unpleasant odor. This water typically has a high concentration of Fe3+ ions, causing the water to turn yellow and become odorous. On the other hand, Muara Sebapo Village has extensive oil palm plantations, which generate solid waste in the form of Empty Palm Fruit Bunches (EFB). Until now, this waste has been underutilized, and in some cases, it has been disposed of or burned. Therefore, efforts are needed to address this issue so that the community can access clean water and utilize waste wisely. In this program, outreach and education are conducted on how to treat well water using solid waste EFB effectively. EFB waste can be transformed into activated carbon, which can be used as a water purification medium in a water treatment unit in the plantation areas and the surrounding community. Activated carbon will act as an adsorbent capable of adsorbing metal ions and organic pollutants present in well water.